(untitled) (Repertorio Científico, 2020)
It was analyzed growth variables using seed disinfectant treatments, in different doses and in two forages commonly used for animal feed (corn and barley), using the FVH technology in the locality from San Carlos, Alajuela, Costa Rica.Products like Kilol® (11 SL), Chlorine (4%) and hydrogen peroxide (10%) were used at a dose of 7.5 ml / L and 5 ml / L, in two types of fodder and the variables evaluated were: production of net biomass, dry matter (MS), crude protein and fungal incidence. Regarding the results, the best treatment for fungal control was T6 (hydrogen peroxide at 5ml / L) for barley, in corn there were no differences. In net biomass production, corn accumulated the greater biomass than barley, with T5 and T6 being the ones with the highest weight and % protein. As for the dry matter content, there is a counterproductive effect when applying disinfectants, since all accumulated less dry matter with respect to the control, possibly due to a phytotoxic effect. The raw protein and dry matter in barley, exceeds the content of a commercial food for animal feed, the kilogram of barley is 3.85 times cheaper. Finally, it is concluded that using hydrogen peroxide at 5ml / L is the best option for seed disinfection, even with a positive effect by promoting germination, growth and accumulation of net biomass. In conclusion, all treatments had a presence of saprophytic fungi, but the corn was the least affected and although they were presented in barley, they were not especially important. The T6 (AO at 5 ml / L) was the one who best controlled fungi in barley. In both corn and barley, the treatments that presented higher values ​​in net biomass production were T5 (AO at 7.5 ml / L) and T6 (AO at 5 ml / L). In both corn and barley, the treatment with the highest values ​​of dry matter was T7 (Witness), there could be a phytotoxicity effect in the other treatments. In both corn and barley, the treatments that presented higher values ​​in protein were T5 (AO at 7.5 ml / L) in corn and T3, T5 and T6 in barley. Oxygenated water in doses of 5 ml / L (T6), had the best effects among the analyzed variables and although in MS and protein it was not, it is within the recommended values ​​for animal feed, according to different authors. In addition, it has a biostimulant effect on seed germination. The results analyzed in the FVH of this investigation, demonstrate to have a greater amount of protein and dry matter than the concentrated food Vap Feed®.